2002
DOI: 10.1037/0278-6133.21.6.615
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study of the effects of expressive writing on psychological and behavioral adjustment in patients enrolled in a Phase II trial of vaccine therapy for metastatic renal cell carcinoma.

Abstract: Forty-two patients with metastatic renal cell carcinoma who were participating in a Phase II clinical trial were randomly assigned to an expressive writing (EW) or neutral writing (NW) group. Patients in the EW group wrote about their cancer, and patients in the NW group wrote about health behaviors. No statistically significant group differences were found in symptoms of distress, perceived stress, or mood disturbance, except for the Vigor subscale of the Profile of Mood States. However, patients in the EW gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
114
1
4

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(124 citation statements)
references
References 22 publications
5
114
1
4
Order By: Relevance
“…Expressive writing studies among non-Hispanic White cancer survivors either used emotional disclosure alone [8,11] or used emotional disclosure prompts first prior to other writing prompts [13]. Similarly, studies using a combination of writing instructions among general populations usually began with giving emotional disclosure prompts first [15][16][17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Expressive writing studies among non-Hispanic White cancer survivors either used emotional disclosure alone [8,11] or used emotional disclosure prompts first prior to other writing prompts [13]. Similarly, studies using a combination of writing instructions among general populations usually began with giving emotional disclosure prompts first [15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple randomized controlled trials also demonstrate that expressive writing delivers promising effects among cancer survivors, such as improving physical symptoms [8,9], pain [10], sleep [11], depressive symptoms [12], and perceived social support [13]. For example, one study randomly assigned 60 breast cancer patients to one of the three conditions [8]: an emotional disclosure condition to write about their deepest feelings and thoughts, a benefit finding condition to write about positive aspects of their cancer experience, and a control group to write about their cancer facts unrelated to emotions.…”
mentioning
confidence: 99%
“…Außerdem steht die klinische Relevanz der Effekte heute deutlich stärker im Zentrum der Aufmerksamkeit, während sich das Paradigma ursprünglich aus einem sozialpsychologischen Hintergrund entwickelt hatte [Pennebaker, 2004;Sloan und Marx, 2004b;Smyth et al, 1999]. Neueren Befunden zufolge geht ES unter anderem einher mit verbesserter Lungenfunktion bei Asthmatikern und verbesserter Gelenksymptomatik bei Rheumatikern [Smyth et al, 1999], weniger Krankenhaustagen bei Patienten mit zystischer Fibrose [Taylor et al, 2003], reduzierten Pflegebedürfnissen und -kosten bei geriatrischen Patienten [Klapow et al, 2001], weniger Arztbesuchen und Symptomen bei Patientinnen mit Brustkrebs [Stanton et al, 2002], weniger Arztbesuchen bei Hochsicherheitsgefangenen [Richards et al, 2000], verbesserter Schlafqualität bei Patienten mit metastasiertem Nierenkarzinom [de Moor et al, 2002], weniger depressiven Symptomen bei leicht depressiven Patienten [Murray et al, 1989;Donnelly und Murray, 1991] und weniger posttraumatischen Belastungssymptomen bei Traumaopfern [Schoutrop et al, 2002]. Wenige Studien fanden keine bzw.…”
Section: Das Schreib-paradigmaunclassified
“…Although research has not yet been conducted on the impact of expressive writing on stress per se, a metaanalysis found that expressive writing was associated with significant improvements in psychological wellbeing (Smyth, 1998), and a number of studies have also found that expressive writing has important effects on mood, including of reduction of depressive symptoms, anxiety, and psychological distress (Pennebaker et al, 1988;Sloan & Marx, 2004b). On the other hand, more recently a number of studies with negative or equivocal findings have been published (e.g., Broderick, Stone, Smyth, & Kaell, 2004;de Moor et al, 2002), and one metaanalytic review of the literature found expressive writing had limited effects in psychiatric versus medical populations (Frisina, Borod, & Lepore, 2004). To date, no previous study has evaluated expressive writing as an intervention for smoking cessation or examined its effect on perceived stress and affect in individuals who attempt to discontinue smoking.…”
Section: Introductionmentioning
confidence: 96%